Effect of concentrate supplementation on ruminal papillae growth and rumen wall development in calves. - Bardales, E. (2024)
The growth of ruminal papillae and rumen thickness in calves subjected to two different feed rations were evaluated. Two homogeneous treatment groups were established, consisting of four individuals each (T1 and T2 ). T1 calves received colostrum, milk, and fresh alfalfa, while T2 calves received the same composition as the first group, supplemented with a concentrated feed. Weaning occurred at 60 days of age for both groups. After weaning, calves were nourished, and rumen wall samples were collected from four anatomical regions of the rumen from each calf. Rumen papillae dimensions were measured macroscopically, and histology was conducted using the paraffin embedding method with H&E staining. T1 calves exhibited average values of 1.38 ± 0.250 mm for papillae length, 3.63±0.245 mm for rumen wall thickness, 1.77 ± 0.312 mm for the muscular layer, and 0.5 ± 0.005 mm for the serosal layer. Conversely, T2 animals achieved an average papillae length of 3.13 ± 0.479 mm, with a wall thickness of 7.13 ± 0.855 mm, a muscular layer thickness of 3.00 ± 0.408 mm, and a serosal layer thickness of 1.02 ± 0.019 mm. In conclusion, the feed ration with concentrate resulted in high values of ruminal papillae growth, together with a remarkable development in the serosal layer, muscular layer, and overall rumen wall in calves.